Metaphysical Poems - Mickiewicz, Adam, 1798-1855 (Brill, 2023)
Adam Mickiewicz (1798 - 1855) was the greatest Polish Romantic poet, and one of the great intellectual and literary figures of the first half of the 19th century in Europe. Through his verses, as well as his efforts as a scholar, lecturer, political activist and literary celebrity, he sought to bridge the gap between the Slavic nations and the culture of Western Europe. This selection of 27 poems focuses on the poems within Mickiewicz's oeuvre which might be described as metaphysical. These original, ingenious verses explore an astonishing range of religious, mystical, philosophical, and existential themes, inviting the reader to include Mickiewicz among the most eminent figures of early European Romanticism, including Coleridge, Wordsworth and Novalis, as well the American transcendentalists. Mickiewicz's poetry and thought are the creation of a restlessly inventive mind: his vision was unorthodox, unpredictable and ever-developing. The book presents a bilingual edition (Polish-English) with a scholarly introduction and commentary, presenting Mickiewicz as a writer in the context of his times. The co-editors of the volume are Jerzy Fiećko, one of the eminent experts in the field of Mickiewicz studies, and Mateusz Stróżyński, an internationally recognized scholar of the Platonic tradition and Western mysticism.